Caregiving, ethnicity and gender in Māori and non‐Māori New Zealanders of advanced age: Findings from LiLACS NZ Kaiāwhina (Love and Support) study. (16th May 2019) - Lapsley, Hilary; Hayman, Karen J.; Muru‐Lanning, Marama Leigh; Moyes, Simon A.; Keeling, Sally; Edlin, Richard; Kerse, Ngaire
Abstract: Objective: This study investigates sex and ethnicity in relationships of care using data from Wave 4 of LiLACS NZ, a longitudinal study of Māori and non‐Māori New Zealanders of advanced age. Methods: Informal primary carers for LiLACS NZ participants were interviewed about aspects of caregiving. Data were analysed by gender and ethnic group of the LiLACS NZ participant. Results: Carers were mostly adult children or partners, and three‐quarters of them were women. Māori and men received more hours of care with a higher estimated dollar value of care. Māori men received the most personal care and household assistance. Carer employment, self‐rated health, quality of life and impact of caring did not significantly relate to the gender and ethnicity of care recipients. Conclusions: Gender and ethnicity are interwoven in caregiving and care receiving. Demographic differences and cultural expectations in both areas must be considered in policies for carer support.